High-quality reference genome and annotation aids understanding of berry development for evergreen blueberry (Vaccinium darrowii). (1st November 2021) - Yu, Jiali; Hulse-Kemp, Amanda M; Babiker, Ebrahiem; Staton, Margaret
Abstract: Vaccinium darrowii Camp (2 n  = 2 x  = 24) is a native North American blueberry species and an important source of traits such as low chill requirement in commercial southern highbush blueberry breeding ( Vaccinium corymbosum, 2 n  = 4 x  = 48). We present a chromosomal-scale genome of V. darrowii generated by the combination of PacBio sequencing and high throughput chromatin conformation capture (Hi–C) scaffolding technologies, yielding a total length of 1.06 Gigabases (Gb). Over 97.8% of the genome sequences are scaffolded into 24 chromosomes representing the two haplotypes. The primary haplotype assembly of V. darrowii contains 34, 809 protein-coding genes. Comparison to a V. corymbosum haplotype assembly reveals high collinearity between the two genomes with small intrachromosomal rearrangements in eight chromosome pairs. With small RNA sequencing, the annotation was further expanded to include more than 200, 000 small RNA loci and 638 microRNAs expressed in berry tissues. Transcriptome analysis across fruit development stages indicates that genes involved in photosynthesis are downregulated, while genes involved in flavonoid and anthocyanin biosynthesis are significantly increased at the late stage of berry ripening. A high-quality reference genome and accompanying annotation of V. darrowii is a significant new resource for assessing the evergreen blueberry contribution to the breeding of southern highbush blueberries.